Artificial intelligence driving intelligent logistics: Benefits, challenges, and drawbacks - Gonçalves, R.; Domingues, L. (Procedia Computer Science, 2025)
This study delves into the transformative potential of Artificial Intelligence (AI) in logistics, focusing on its capacity to usher in an era of Intelligent Logistics. It examines the benefits, challenges, and drawbacks associated with AI’s integration, portraying it as a pivotal shift towards unprecedented efficiency, innovation, and strategic advantage. The study emphasizes that while AI can significantly optimize operations, reduce costs, and enhance customer service, it also brings forth complex challenges such as legal liability concerns, complex business ecosystems, and significant resource allocation, alongside notable drawbacks. For instance, the existence of cybersecurity vulnerabilities, dependency on historical data, and the risk of workforce displacement. Current literature tends to focus on specific implementations and their impacts rather than providing a general overview. Via a Multivocal Literature Review composed of a Systematic Literature Review complemented by a review of grey literature, this research addresses this gap by providing a nuanced view of how AI is reshaping logistics. By gathering and synthesizing diverse insights from various implementations, this study offers a holistic analysis of AI’s impact. Through this comprehensive and in-depth analysis, the study aims to equip businesses with the necessary insights for informed decision-making regarding AI adoption in logistics, ensuring a balanced and effective integration of technology to meet evolving industry standards and demands.